Gut dysfunction in the ICU: diagnosis and management. Issue 2 (April 2021) - Chapple, Lee-anne S.; Plummer, Mark P.; Chapman, Marianne J.
Abstract : Purpose of review: Progress has been made in our understanding of gut dysfunction in critical illness. This review will outline new findings and give perspectives based on previous knowledge and concurrent advances in nutrition. Recent findings: The relationship between gut dysfunction and poor outcomes in critical illness has received considerable interest. It remains uncertain whether gut dysfunction is merely a marker of illness severity or if it is directly responsible for prolonged critical illness and increased mortality. This relationship is difficult to ascertain given there is no agreed method for identification and quantification; biomarkers such as intestinal fatty acid binding protein and citrulline show promise but require further study. Recent studies have investigated strategies to deliver enteral nutrition targets with impacts on gut function, including high calorie or protein formulae, intermittent regimes and novel prokinetics. Summary: Gut dysfunction is associated with poor outcomes, but it remains uncertain whether strategies to improve gut function will influence survival and recovery.